The Rationality of Drug Therapy in Pulmonary Anti-Tuberculosis Patients at Puskesmas Cimahi Tengah - Linda Purnamawati Suherman; Muhammad Abdul Rozzaaq; Robby Ramdani; Riza Amelia; Faizal Hermanto; Vina Septiani; Alfi Nurul Islamiyah (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2025)
Background: Tuberculosis (TB) is a significant global health challenge in Indonesia. The rational use of anti-TB drugs is essential for treatment success and for preventing drug resistance in patients with TB. Objectives: This study aimed to evaluate the rationality of anti-TB drug use in patients with pulmonary TB at the Cimahi Tengah Public Health Center (Puskemas Cimahi Tengah). Methods: This research employed a descriptive method with a retrospective approach based on observational data from the Tuberculosis Information System (SITB) between January and December 2023. Samples were selected using purposive sampling based on the predefined inclusion and exclusion criteria. Results: The results showed that All patients (100%) received treatment according to the national guidelines and WHO recommendations, including the HRZE regimen (rifampicin, isoniazid, pyrazinamide, and ethambutol). The accuracy of indication, drug selection, dosage, and administration intervals also reached 100%, demonstrating adherence to the clinical standards. Conclusion: Anti-TB drug use at the Cimahi Tengah Public Health Center complies with established treatment standards, ensuring treatment effectiveness and contributing to optimal patient outcomes.